PENGARUH PENGGUNAAN LKPD BERBASIS MIND MAP PADA PEMBELAJARAN BERBASIS MASALAH TERHADAP PENCAPAIAN KOMPETENSI FISIKA PESERTA DIDIK KELAS XI SMA NEGERI 2 PADANG PADA MATERI TEORI KINETIK GAS DAN PEMANASAN GLOBAL - Widia Ramanda Putri; Masril Masril; Gusnedi Gusnedi (Universitas Negeri Padang, 2017)
One of the factors causing the low achievement of Physics competence of learners is the completeness of the teaching materials used such as LKPD is not adequate. One of the learning models that can be done to improve the competence of learners is Problem Based Learning. This study was conducted to determine the effect of using LKPD based on the mind map of problem based learning on the achievement of the competence of physics students of class XI SMA Negeri 2 Padang.This type of research is quasi experimental (Quasi Experimental Research) with research design The Randomized Postest - only Control Group Design, using Matched Subjects. The study population is all students of class XI SMA Negeri 2 Padang registered in the academic year 2016-2017, which is 7 classes of academic year 2016/2017. The sample of research was taken with Purposive Sampling technique. The research data consisted of attitude, knowledge and skill competency data, which instrument was used are observation sheets, a written test and performance assesment rubric. The three competencies was analyzed by using t- test at real level of 0,05. Knowledge and skill competence also analyzed by simple linear regression test, and correlation test at significant level 5 %. Research data is the value of learning outcomes of learners attitude competence, knowledge and skills and the value of LKPD based mind mapping. The research instrument is an observation sheet for measuring the attitude competence, the final test to measure knowledge competence and performance rating sheet to measure the competency of the skill. Research data were analyzed by two-equation equality test and regression test and correlation. The two-point equality test was performed for all competencies in both sample classes. Regression and correlation test is performed for knowledge competence and skill competence in experiment class and LKPD value based on mind map. Through correlation test obtained significance level of relationship that is, the first value with the value LKPD knowledge competency-based mind map is a powerful, with a percentage contribution LKPD mind map based on the achievement of physical competence of learners by 29.5% and the remaining 70.5% is influenced by other variables . LKPD based on mind map also has a significant influence on the competence of students' skills